KARAKTERISTIK PENDERITA HIPERTENSI DENGAN KOMPLIKASI YANG DIRAWAT INAP PUSEKESMAS TANJUNG BALAI KARIMUN TAHUN 2010-2012 - agustina sianipar; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
AbstractThe diseases is not contagious is the leading cause of death globally. Hypertension became a public health problem if not controlled will evolve and give rice to complication harmfull. According to the World Health Organization (WHO) report, hypertension was the cause of death in the world the number 1. Data RSUP Pirngadi Medan, the number cases of hypertension in 1999 as many as 122 cases with proportion 0,8% and 2000 in creased to 215 cacses with proportion of 1,5%. To know the characteristics of people with hypertension with complication the admitted in Tanjung Balai Karimun Puskesmas in 2010-2012, has been doing research is a descriptive case series continued with statistical analysis. The sample numbered 107 data hypertension with complication which admitted.From the data recorded the largest proportion of sufferers results obtained on age >60 years (60,7%), and sex women (56,1%), the malays (43%), Islamic (67,3%), no school (28%), the house wives (43,9%), merried (91,6%), at West Sei Lakam (19,6%), teightness (44,9%), deggre 2 (72,0%), heart diseases (75,7%), long treatments on average 2,97 days, common (56,1), PBJ (54,2%).There is a difference between long which means the average treatments based on the complications of hypertension. (p=0,000). Parties puskesmas can provide counseling to the family of patien to be more quickly responsiveness to complaints and such symptoms the occurrence of a complication early in order to minimize the occurrence of complication heavier and monitor patiens in consuming to a drugs with true to his blood preassure stables and willing to be refreanced when at puskesmas can’t be addressed. Expected in the clinics in order to supplement the data relating to patients, especially patiens with hypertension complication to health workers to provides counseling to the patient, family and community about healthy living patterns.Keyword : Hypertension, characteristic of patiens, Puskesmas Tanjung Balai Karimun